2018
DOI: 10.1155/2018/4938649
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis of Candida albicans Inhibits Autophagic Flux in Macrophages

Abstract: Autophagy machinery has roles in the defense against microorganisms such as Candida albicans. Lipidated LC3, the marker protein of autophagy, participates in the elimination of C. albicans by forming a single-membrane phagosome; this process is called LC3-associated phagocytosis (LAP). However, the influence of C. albicans on autophagic flux is not clear. In this study, we found that C. albicans inhibited LC3 turnover in macrophages. After the phagocytosis of C. albicans in macrophages, we observed fewer acrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…In contrast to classical phagocytosis cups, those formed during LAP contain several autophagy proteins (Kim et al, 2013;Panneerdoss et al, 2017;Duan et al, 2018). Thus, Beclin1 and ATG5 proteins are known to be recruited to phagosomal membranes as a very early event in LAP (Martinez et al, 2011;Kim et al, 2013;Li et al, 2013).…”
Section: Uptake Of Apoptotic Substrates By Gc Engages Autophagy Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to classical phagocytosis cups, those formed during LAP contain several autophagy proteins (Kim et al, 2013;Panneerdoss et al, 2017;Duan et al, 2018). Thus, Beclin1 and ATG5 proteins are known to be recruited to phagosomal membranes as a very early event in LAP (Martinez et al, 2011;Kim et al, 2013;Li et al, 2013).…”
Section: Uptake Of Apoptotic Substrates By Gc Engages Autophagy Proteinsmentioning
confidence: 99%
“…In our KGN cell model, we observed an increase of the expression of ATG5 protein during phagocytosis of apoptotic oocytes, while those of ATG7 did not vary. The formation of phagocytic cups and the ingestion of apoptotic substrates progress through activation of a downstream effector, Ras-related C3 botulinum toxin substrate (RAC1), which mediates actin reorganization (Kim et al, 2013;Teplova et al, 2013;Panneerdoss et al, 2017;Duan et al, 2018). While the order of events in the signaling pathways remains an A c c e p t e d m a n u s c r i p t unaddressed question (Heckmann et al, 2017), the recruitment of autophagy proteins seems to be necessary to sustain MERTK-mediated ingestion.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Furthermore, cell apoptosis was increased in K1 and SW579 cells following GINS2 silencing by in situ fluorescence detection. Previous studies have demonstrated that in situ fluorescence assay can verify the change of apoptosis rate ( 38 , 39 ). Alternatively, caspase-3 activity and other techniques can also be applied for cell apoptosis assay, which will be performed in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…La LAP joue un rôle essentiel au cours des infections fongiques. Elle a été décrite notamment dans le cas d'infections par les champignons Aspergillus [24], Candida albicans [25], Saccharomyces cerevisiae [5] ou Rhizopus spp [26]. Ainsi, suite à leur phagocytose, les conidies d'Aspergillus fumigatus, spores assurant la multiplication du champignon, gonflent, exposant alors en surface des β-glucanes, sucres habituellement masqués par sa paroi, qui sont reconnus et activent la cellule [24] par la voie Dectine-1-Syk-NOX2.…”
Section: Les Champignons Et Les Parasitesunclassified